Unconventional Monetary Policy Shocks in the Euro Area and the Sovereign-Bank Nexus - Nikolay Hristov; Oliver Hülsewig; Johann Scharler (Center for Economic Studies and ifo Institute (CESifo), 2020)
We explore the effects of the ECB's unconventional monetary policy on the banks' sovereign debt portfolios. In particular, using panel vector autoregressive (VAR) models we analyze whether banks increased their domestic government bond holdings in response to non-standard monetary policy shocks, thereby possibly promoting the sovereign-bank nexus, i.e. the exposure of banks to the debt issued by the national government. Our results suggest that euro area crisis countries' banks enlarged their exposure to domestic sovereign debt after innovations related to unconventional monetary policy. Moreover, the restructuring of sovereign debt portfolios was characterized by a home bias.
Keywords: C32; E30; E52; E58; G21; H63; 330; European Central Bank; unconventional monetary policy; panel vector autoregressive model; sovereign-bank nexus